FILM INDUSTRY AS BRANCH OF CREATIVE ECONOMY OF SPAIN AT THE BEGINNING OF THE XXI CENTURY - E. . Belova (Ибероамериканские тетради, 2016)
The creative industries have one of the highest rates of the development in the modern economy. Researchers consider that these industries contain potential for the socio-economic development of countries and cities. The article examines the contribution of the creative industry to the economy of European Union countries. The research contains metodology of the selection and the analysis of key indicators of the cinema industry development of Spain (as one of the leader countries in the world in this field). The result of the work represents the classification of autonomous communities of Spain according to the development of local industry.